2017
DOI: 10.3390/molecules22010164
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Strawberry Extract against Inflammatory Stress Induced in Human Dermal Fibroblasts

Abstract: A protracted pro-inflammatory state is a major contributing factor in the development, progression and complication of the most common chronic pathologies. Fruit and vegetables represent the main sources of dietary antioxidants and their consumption can be considered an efficient tool to counteract inflammatory states. In this context an evaluation of the protective effects of strawberry extracts on inflammatory stress induced by E. coli LPS on human dermal fibroblast cells was performed in terms of viability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 58 publications
4
15
0
Order By: Relevance
“…Similar effects were obtained when Manuka honey was used as a therapeutic agent against AAPH induced oxidative stress in HDF cells by reducing intracellular ROS production and NO 2 − accumulation [ 11 ]. Also, pre-treatment with strawberry extracts have been demonstrated to counteract the oxidative damage induced by different chemical and biological agents such as hydrogen peroxide [ 15 ], ultraviolet radiations [ 16 ], and lipopolysaccharide [ 7 , 8 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar effects were obtained when Manuka honey was used as a therapeutic agent against AAPH induced oxidative stress in HDF cells by reducing intracellular ROS production and NO 2 − accumulation [ 11 ]. Also, pre-treatment with strawberry extracts have been demonstrated to counteract the oxidative damage induced by different chemical and biological agents such as hydrogen peroxide [ 15 ], ultraviolet radiations [ 16 ], and lipopolysaccharide [ 7 , 8 ].…”
Section: Resultsmentioning
confidence: 99%
“…Oxidative stress represents the main cause of most common chronic diseases including inflammation, cardiovascular diseases, diabetes, metabolic syndrome, and cancer [ 6 ]; in recent years, numerous studies have demonstrated that dietary antioxidants from plant foods represent an efficient strategy to counteract this condition, and can be considered a useful tool for the maintenance of human health status and well-being conditions [ 7 , 8 , 9 , 10 ]. On the experience of our previous reports [ 7 , 8 , 9 , 10 ] and the antioxidant potential of MUD1 (it presents 1435.66 ± 71.78 mg/100 g and 295.84 ± 14.80 mg/100 g of Total phenolic content and total flavonoids content, respectively) [ 2 ], in the present study we evaluated the efficacy of beeswax by-products, MUD1, as a potential therapeutic agent against oxidative damage induced by 2,2′-aszobis(2-amidinopropane) dihydrochloride (AAPH) in Human Dermal Fibroblasts (HDF). HDF are considered an excellent model system to study several aspects of cell physiology, and are widely used to evaluate the in vitro effect of substances of interest in the prevention of oxidative damage caused by different agents [ 8 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the last few years, the effects of strawberries against the inflammatory condition have been investigated through many in vitro and in vivo studies. In different lipopolysaccharide (LPS)‐treated cellular models, such as mouse macrophages and human dermal fibroblasts, strawberry treatment led to the downregulation of mitogen‐activated protein kinases (MAPK) and NF‐κB signaling pathways, consequently reducing the levels of inflammatory cytokine levels, the production of nitric oxide (NO), and the expression of inducible nitric oxide synthase (iNOS) and increasing anti‐inflammatory cytokines. In addition, an improvement of mitochondrial functionality and antioxidant enzyme activities by modulation of the adenosine monophosphate (AMP)‐activated protein kinase pathway has also been detected …”
Section: Strawberry and Inflammationmentioning
confidence: 99%
“…These pro-inflammatory cytokines are mainly produced by immune cells, i.e., macrophages and lymphocytes, when they are exposed to inflammatory stimuli [ 19 ], and by gingival fibroblasts and the PDL, which functions as a physical barrier after stimulation with bacterial components or inflammatory mediators, including IL-1β [ 20 , 21 , 22 ]. Thus, many studies have been focusing on identifying molecules, synthetic chemicals, or natural compounds that can suppress the production of inflammatory cytokines to control periodontal inflammation [ 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%